Pre-transplant achievement of negativity in minimal residual disease and French–American–British L1 morphology predict superior outcome after allogeneic transplant for Philadelphia chromosome positive acute lymphoblastic leukemia: an analysis of Southeast Asian patients. Issue 5 (May 2015) - Ma, Liyuan; Hao, Siguo; Diong, Colin; Goh, Yeow-Tee; Gopalakrishnan, Sathish; Ho, Aloysius; Hwang, William; Koh, Liang-Piu; Koh, Mickey; Lim, Zi-Yi; Loh, Yvonne; Poon, Michelle; et al.
Abstract To better understand predictive factors and improve the clinical outcome of allogeneic transplant for patients with Philadelphia positive acute lymphoblastic leukemia, we analyzed 67 Southeast Asian patients transplanted in our institutions. Multivariate analysis showed that disease status before transplant, year of transplant and, interestingly, French–American–British (FAB) subtype had a significant impact on overall survival (OS) and non-relapse mortality. Patients who were minimal residual disease (MRD) negative at transplant had a 3-year OS of 73% compared to those who were MRD positive (45%) and refractory (0%). The 3-year cumulative incidence of relapse was 18% and 36% for the MRD negative and positive groups, respectively. FAB L1 subtype had a significantly superior 3-year OS of 63% vs. 29% for L2 subtype. Pre-transplant use of a tyrosine kinase inhibitor significantly improved outcomes in univariate but not multivariate analysis, as it served to induce more patients into MRD negativity, which was the factor that directly improved transplant outcome.